Magnetoelectric soft composites with a self-powered tactile sensing capacity. (March 2020) - Zhang, Xuan; Ai, Jingwei; Ma, Zheng; Du, Zhuolin; Chen, Dezhi; Zou, Ruiping; Su, Bin
Abstract: Relative movement between magnets and conductive wires can generate electricity, known as electromagnetic induction. Electromagnetic induction can endow soft electronic devices with a self-powered capacity. However, such a design is difficult to achieve due to the rigid feature of magnets. Crushing magnetic bulks into powders can effectively decease their Young's modulus, allowing for the generation of new type self-powered soft electronic devices. Here we demonstrated the fabrication of magnetoelectric type soft composites with a self-powered tactile sensing capacity. Magnetic powders, instead of magnets, were dispersed in the polymeric elastomer, allowing for an anisotropic mechanoelectrical conversion by fixing a conductive helix in proper positions. Maxwell numerical simulation was used to investigate the sensing mechanism, and to guide further improvement of their mechanoelectrical converting performances by tuning different experimental factors. Furthermore, mechanoelectrical converting outputs by the assembly of several magnetoelectric type soft composites are also observed, enabling them to work as a smart timer for precisely recording the car parking. We anticipate that the presented design principle will advance and inspire the development of new type soft tactile sensors and their integration into complex self-powered sensing systems. Graphical abstract: Image 1 Highlights: Magnetoelectric soft composites with a self-powered sensing capacity are proposed. Sensing fundamental mechanisms are investigated by the Maxwell simulation. Diverse parameters to improve the self-powered capacity are discussed. Promising application of magnetoelectric soft composites are demonstrated.